2011
DOI: 10.1292/jvms.10-0454
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Ku70-Deficient Lung Epithelial Cell Lines and Their Hypersensitivity to Low-Dose X-Irradiation

Abstract: ABSTRACT. In clinical situations, cellular resistance to chemotherapy and radiotherapy is a significant component of tumor treatment failure. The DNA repair protein Ku70 is a key contributor to chemoresistance to anticancer agents, e.g., etoposide and bleomycin, or radioresistance. Ku70 plays a key role as a sensor of DNA double-strand breaks (DSBs) induced following exposure to ionizing radiation as well as treatment with some chemotherapeutic drugs. The responses of different organs to radiation vary widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 30 publications
5
16
0
Order By: Relevance
“…First, we confirmed the expression of Ku70. Consistent with our previous study [12], Western blot analysis showed that Ku70 was expressed in control (Ku70 +/−) MLE cells, but not in Ku70 −/− MLE cells (Fig. 1A).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…First, we confirmed the expression of Ku70. Consistent with our previous study [12], Western blot analysis showed that Ku70 was expressed in control (Ku70 +/−) MLE cells, but not in Ku70 −/− MLE cells (Fig. 1A).…”
Section: Resultssupporting
confidence: 92%
“…Previously, our findings revealed that Ku70 −/− MLE cells are markedly sensitive to X-irradiation at low doses, from 0.125 to 2 Gy as compared with Ku70 +/− MEL cells (control cells) [12], suggesting that Ku70 plays a key role in radioresistance at doses lower than 2 Gy in lung epithelial cells. However, it remains unclarified whether Ku70 plays a role in radioresistance at doses higher than 2 Gy and works as an inhibitor of radiation-induced death of lung epithelial cells.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations